Demonstration of Millimeter Wave 5G Setup Employing High-Gain Vivaldi Array. (23rd April 2018) - Sethi, Waleed Tariq; Ashraf, Muhammad Ahmed; Ragheb, Amr; Alasaad, Amr; Alshebeili, Saleh A.
Abstract : We present a 4 × 4 slot-coupled Vivaldi antenna (SCVA) array unit cell, which offers wide bandwidth and high gain ( 23 dBi) at the millimeter wave (mmW) frequencies of 28 GHz and 38 GHz. A single SCVA element is first presented, which has a bandwidth of 25–40 GHz with an average gain of 13 dBi at the frequencies of interest. This antenna element is then used to design a 1 × 4 linear SCVA array matched to a 50 Ω impedance via a modified Wilkinson power divider (WPD). Next, the 1 × 4 linear array is used to construct a 4 × 4 antenna array unit cell. The proposed 4 × 4 antenna array unit cell is fabricated, and the characteristics of its elements (i.e., the single SCVA, 1 × 4 linear array, and WPD) are thoroughly investigated. Further, the 4 × 4 array is tested for signal reception of various digital modulation formats at lab environment using high-speed digital signal oscilloscope. In particular, a 2.5 Gbps data rate is successfully transmitted achieving receiver sensitivity of −50 dBm at 2 × 10 −3 bit error rate (BER) for 32 quadrature amplitude modulation (QAM) with a system baud rate of 500 MHz. The wide bandwidth and high gain along with the excellent performance of the proposed 4 × 4 antenna array unit cell makes it an excellent candidate for future 5G wireless communication applications.